PERAN PENGAWASAN PERKEMBANGAN PERUSAHAAN TEKNOLOGI KEUANGAN PEER-TO-PEER LENDING YANG BELUM TERDAFTAR OLEH OTORITAS JASA KEUANGAN - Elahi Fikri, Faisal; Ratnawati, Elfrida (Ensiklopedia of Journal, 2023)
The development of law and technology is always developing, if new technology emerges, new laws will emerge. As one example is the existence of financial technology that has emerged as a differentiator from the conventional banking system. One of them is P2P lending or online loans. Online loans are intended to make it easier to lend money and return it. Behind the facilities provided there are things that cause harm to users such as high interest rates, unregistered legality, and even have the potential to commit crimes such as defamation, intimidation of billing, and death threats. This study uses a normative legal approach, which is based on relevant legal literature, such as books, relevant laws and regulations according to the topics discussed. To maintain the continuity of the development of financial technology, a good legal system is needed to monitor and maintain proper law enforcement in accordance with positive law. so that the role of government oversight is needed through the Financial Services Authority, law enforcement officials, the investment alert task force, and the role of the public in using financial technology services as an ideal form of legal system adapted to the realities that exist in Indonesian society.Keywords: Finansial Technology, financial technology services Authority, Online Loans